Measurement of Energy Poverty with a Multidimensional Approach: A Systematic Literature Review - Fernández, Karen; Lezcano, Laine; González, Arturo (Revista INVI, 2023)
Energy Poverty (EP) is an economic and social phenomenon related to energy variables. They can be unidimensional and multidimensional. This study provides a systematic literature review of EP in order to know the main definitions, metrics, indicators, constraints, advantages and disadvantages of the multidimensional approach. A methodology consisting of a succession of well-defined steps was presented where research questions were posed and answered through the identification, selection, data extraction and classification of bibliographic documents in a systematized manner that addressed Multidimensional EP in the period 2005-2023. The main findings indicate that in the world, studies on EP are concentrated to a major extent in Europe, as is collaboration in scientific writing. However, in recent years, studies on EP and its applications have been identified in Latin America and the Caribbean, especially with a multidimensional approach. Thus, both the conceptualizations and metrics of Multidimensional EP are diverse, heterogeneous and with a notable lack of consensus on them.